Hello from MrBillDoesMath!
Answer: infinite solutions
Discussion: I did a double take on this one but the left hand is
a + 3 + 2a = 3a +3
and the right hand side is
-1 + 3a + 4 = 3a + (4-1) = 3a + 3
The left and right sides of the equation are identical for all "a", i.e. for infinitely many "a" values.
Regards, MrB.
Answer:
Expand: x² + 11x + 11x + 121
Simplify: x² + 22x + 121
Step-by-step explanation:
To expand this, you can use the FOIL technique:
First terms
Outer terms
Inner terms
Last terms
(x+11)(x+11)
F - x*x = x²
O - x*11 = 11x
I - 11*x = 11x
L - 11*11 = 121
Put these numbers together (expanded) to get:
x² + 11x + 11x + 121
Put the common terms together (simplify) to get:
x² + 22x + 121
Note:
Not sure if you need this info, but (x + 11)(x + 11) is the same as (x + 11)².
The numbers need to be in the order I put them in because you are supposed to place them in order greatest to least degree.
Hope it helps!
Whats the problem you need help with
Answer:
View graph
Step-by-step explanation:
The population refers to the whole set under study, while the sample is a representative part of that population.
Factoring f(x) would give a factor (x-1-2i), so you can divide f(x) by this, leaving (x-3)(x+4)(x-1+2i), so the other roots are:
x=3
x=-4
x=1-2i